Counselling approaches and characteristics of recovering substance use disorder counsellors working in addiction treatment agencies in New York, USA - Shaari, Azahah Abu Hassan; Razak, Ateerah Abdul; T S, Tuan Muhammad Zukri; Alghamdi, Ibrahim (Nurture, 2024)
Purpose: The objective of this qualitative study is to investigate the perspectives of recovering counsellors on counselling approaches and the influence that their personal attributes have on clients. Design/Methodology/Approach: Purposive and snowball sampling techniques were utilised, and semi-structured face-to-face interviews were carried out with 18 recovering counsellors in New York, USA. Thematic analysis was employed to analyse the data. Findings: Motivational interviewing (MI), and cognitive behavioural therapy (CBT), and support groups were popular therapeutic modalities among many participants. Recovering counsellors underlined that utilising personal qualities contributed positively to treatment outcomes by establishing a long-lasting relationship with clients. Conclusion: This study’s findings underscored the significance of exploring recovering SUD counsellors’ viewpoints regarding their counselling approaches and personality traits in underscoring their role in providing treatment services to clients. Research Limitations: The study reflects recovering counsellors’ perspectives at a specific moment, but the dynamic nature of recovery implies that their views and approaches may evolve over time, affecting the long-term implications of their counselling methods. Practical Implications: Organizations may consider providing supervision to recovering counsellors, acknowledging the challenges they face, and leveraging their personal qualities for better client engagement. Contribution to Literature: The study’s emphasis on therapeutic modalities and personal qualities provides practical insights for optimizing counselling approaches and maximizing the benefits of employing recovering counsellors in SUD treatment settings.